Character Building in Teaching English Vocabulary For Elementary School Students - Rosi Kumala Sari; Dwi Megista Putri; Mona Afersa (Jurnal Pendidikan Sultan Agung, 2023)
The aim of this research was to describe the activity of C-L-C (Central Learning and Character) program in buiding character and improving English vocabulary of Elementary School Students. C-L-C Programme has created integrated learning acvities to build students’ character and improve English vocabulary for elementary  school students. The design of this study was a descriptive qualitative research. The researcher described the activities of English insrtuctor and students in building students’character and improving English vocabulary. There was 23 elementary School students had joinned on C-L-C program. The techniques for collecting the data were observation, documentation and questionnaire. The finding of this study showed that some activities did by the English instructor on C-L-C program to build the students’ character and improve the students’ English vocabulary were reading a text, writing, painting, gaming, pronouncing the new vocabulary, retelling the story, disscussing the character value in the story and preparing the students’ characters’ book. The result of this study, the C-L-C programme had built students’ character on discipline, responsibility, honor the other people and care to the environmen. Besides C-L-C had improved the students’ English vocabualry. It can be seen from the participation of students in learning process and the recapitulation of the students’ English test score. It showed that 1 students was poor, 5 students were satisfactory, 8 students were good and 9 students were very good. It can be concluded that C-L-C programme built students’ character and improved the students’ English vocabulary.  Keywords:  Character Building , teaching English vocabulary